COVID-19 financial aid and productivity: Has support been well spent? - Carlo Altomonte; Maria Demertzis; Lionel Fontagné; Steffen Müller (Bruegel, 2021)
Most European Union countries have made good progress with vaccinating their populations against COVID-19 and are now seeing a rebound in economic activity. While the scarring effects of the crisis and the long-term implications of the pandemic are only partially understood, the effects of support given to firms can be evaluated in order to help plan the removal of crisis support. European regions and countries that depend heavily on services requiring physical proximity have been hit hardest by COVID-19-related measures. But these services sectors tend also to be the smallest and least-productive in any economy, implying that, coming into the crisis, the highest shares of zombie firms were in these sectors. Reliance on physical proximity and the higher incidence of zombies to start with have combined to make those services-dependent economies particularly vulnerable to any attempt to remove the support put in place during the pandemic. The evidence shows that the main goal of the provision of support during the COVID-19 crisis, namely to protect employment, has been achieved. However, the evidence is varied on how efficiently this was done, in terms of helping firms that have a good chance of surviving, while not supporting those that will in any case exit. An analysis of France, Germany and Italy shows the potential for "cleansing effects" in that it was the least-productive firms that have been affected most by the crisis. While support was generally not targeted at protecting good firms only, financial support went by and large to those with the capacity to survive and succeed. Labour schemes have been effective in protecting employment.
Keywords: 330; financial crisis; eu governance; Covid-19